Pengaruh Citra Merek dan Harga terhadap Loyalitas Pengguna Iphone Dimediasi oleh Kepercayaan Merek (Studi pada Mahasiswa Kota Malang) - Dwi Satrio; Kartika Anggraeni Sudiono Putri (Universitas Batanghari Jambi, 2023)
This study focuses on knowing the effect of a brand image and price on Iphone user loyalty with brand trust as a mediating variable among college students in Malang City. This research uses quantitative methods, the number of samples used in this study is 112 respondents with probability sampling. The method of collecting data by distributing questionnaires is measured using a Likert. The data analysis technique in this study is using component-based SEM using PLS through software SmartPls. The results showed that brand image variable has a significant effect on customer loyalty, price has a significant effect on customer loyalty, brand image has a significant effect on brand trust, price has a significant effect on brand trust, brand trust has a significant effect on customer loyalty, brand trust is able to mediate the effect of brand image on customer loyalty, brand trust is able to mediate the effect of price on customer loyalty.